2021
DOI: 10.3892/mmr.2021.11893
|View full text |Cite
|
Sign up to set email alerts
|

Critical implication of the PTEN/PI3K/AKT pathway during BMP2-induced heterotopic ossification

Abstract: Heterotopic ossification (HO) is characterized by extraskeletal ossification in soft tissue. Thus far, there is a lack of effective drug therapy against HO. Loss of PTEN in osteoblasts has been reported to accumulate bone mass in skeletal development and promote fracture healing in association with the activation of the PI3K/AKT pathway. However, the role of the PTEN/PI3K/AKT signaling in HO pathogenesis remains unknown. The present study investigated the implication of this pathway during BMP2-induced osteoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…A similar inverse association was also demonstrated between PTEN and BMP2 [46] in the C3H10T1/2 cell line. PTEN inhibited the BMP2-induced osteoblast differentiation of MSCs at the osteoblast lineage commitment level and at the early and late stages of osteogenic differentiation, while BMP2 repressed PTEN expression, leading to the activation of PI3K/AKT and to osteogenesis.…”
Section: Pten Genesupporting
confidence: 72%
See 1 more Smart Citation
“…A similar inverse association was also demonstrated between PTEN and BMP2 [46] in the C3H10T1/2 cell line. PTEN inhibited the BMP2-induced osteoblast differentiation of MSCs at the osteoblast lineage commitment level and at the early and late stages of osteogenic differentiation, while BMP2 repressed PTEN expression, leading to the activation of PI3K/AKT and to osteogenesis.…”
Section: Pten Genesupporting
confidence: 72%
“…The authors studied the role of the PTEN/PI3K/AKT signaling pathway in ectopic calcification by establishing a specific animal model via the implantation of human recombinant BMP2 into the muscle tissue of mice to induce soft tissue ossification. The inactivation of the PI3/AKT signaling, by PTEN, markedly suppressed the BMP2-induced ectopic endochondral calcification of muscles [46].…”
Section: Pten Genementioning
confidence: 96%
“…Although BMP2 is not a chemokine, it plays an important role in the evolution of local inflammatory responses. Studies have reported that BMP2 can induce osteoblast differentiation and proliferation 41 and enhance cell migration and invasion 42 . BMP2 also plays a role in the treatment of inflammatory joint diseases by regulating the PI3K/AKT signaling pathway 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, heterotopic ossification (HO) model is suitable for estimating osteoinductive effect of scaffolds in vivo , which consists of ectopic bone formation within soft tissues following surgery or trauma ( Shimono et al, 2011 ). Muscle pouch model is usually as a HO model and used to estimate ectopic bone-formation of scaffolds with or without medicine ( Dong et al, 2021 ). In this study, an improved heterotopic ossification model was a unilateral femoral eccentric femoral defect model with the destruction of cortical bone and overflow of bone marrow, which brought much more macrophages from bone marrow compared to the muscle pouch model ( Figure 3A ).…”
Section: Discussionmentioning
confidence: 99%